Design of Saving and Loan Cooperative Application at BMT Amal DD cooperative - Hendrawan, Aditya; Ayuningtyas, Ayuningtyas; Arrosyidi, Achmad (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
BMT Amal DD cooperative as a syari’ah financial cooperative working a credit unit activity. The process of writing and transaction of the members still uses manual way that is by writing transaction of the members in a big book transaction. This causes many problems, such as the difficulty in finding the transaction of the members because the coorperation clerk has to find the transaction data one by one in every transaction book. Besides that, the calculation process of the monthly instalment and the division of profit can cause new problems. Based on the existing problem, it is needed saving and loan cooperative application which can help solve the problems in BMT Amal DD cooperative. The saving and loan cooperative application will assist the cooperative clerk in finding the data of members transaction, calculating montly instalment, calculating the division of the profit as well as helping to make financial report. The application of saving and loan cooperative can manage the transaction data in BMT Amal DD cooperative resulting information in the form of members saving transaction, cost transaction report, instalment payment report, operational cost transaction report, profit division report, general journal report, general ledger, balance report, and lost and profit report.